Indicadores geobiofísicos de suscetibilidade à desertificação aplicados aos sistemas ambientais na sub-bacia do riacho Juriti, município de Canindé-CE - Pessoa, Elen Karine Forte (2023)
The preservation or degradation of nature is related to the way energy and matter is distributed and concentrated in ecosystems. Thus, the vulnerability of these systems to desertification processes depends largely on the natural dynamics of the environment, which is governed by the flows of matter and energy. From the context of the semi-arid Ceará, it can be assumed that certain components play crucial roles in the dynamics of matter and energy. According to the assumptions of the Ecodynamic Theory, the vegetation cover, by being able to intercept and dampen the energy forces, together with the use and coverage of the soil are fundamental components in this process. They can activate or minimize degradational processes. Therefore, the research proposed to evaluate the susceptibility of the environmental systems to desertification in the Juriti Creek sub-basin - Canindé/CE, in the light of the assumptions of the Ecodynamic Theory, in order to understand the contribution of this theory to the selection of Geo-Biophysical Indicators of Desertification (GBDI). The operational procedure employed in the methodology was the thematic mapping, in which occurred the inference of information for delimitation of environmental systems, application of the IGBD and production of the map of the levels of susceptibility to desertification of the sub-basin and the map of emerging and potential susceptibility of the systems. The results revealed that the adaptation of the IGBD to the Ecodynamic Theory, when applying indicators related to vegetation, show a sub-basin with susceptibility levels to desertification from moderate to high, where the highland systems with greater vegetation density present a potential susceptibility, therefore, if the vegetation is removed the susceptibility level may increase, while the highland systems presented an emerging susceptibility, requiring mitigation measures that include the integration of native vegetation to agricultural systems. It can be concluded that integrating vegetation indicators to the IGBD contributes to the analysis of desertification in different environmental systems, helping to define the levels of susceptibility and its classification into Potential and Emergent.